2018
DOI: 10.1128/aem.00610-18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ceftiofur and Chlortetracycline on the Resistomes of Feedlot Cattle

Abstract: Treatment of food-producing animals with antimicrobial drugs (AMD) is controversial because of concerns regarding promotion of antimicrobial resistance (AMR). To investigate this concern, resistance genes in metagenomic bovine fecal samples during a clinical trial were analyzed to assess the impacts of treatment on beef feedlot cattle resistomes. Four groups of cattle were exposed, using a 2-by-2 factorial design, to different regimens of antimicrobial treatment. Injections of ceftiofur crystalline-free acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
4
29
1
Order By: Relevance
“…In our study, isolates were not resistant to azithromycin, ceftiofur, or ceftriaxone either before or after either ceftiofur or tulathromycin treatment. This result was supportive of metagenomic data analyses conducted by Weinroth et al and Doster et al but counter to the findings of Alali et al (33)(34)(35). The studies measured the effect of either ceftiofur or tulathromycin treatment on the microbiome and/or resistome of the fecal community of beef cattle; however, none of the studies focused directly on culturable bacteria, let alone Salmonella, as the outcome bacteria of interest.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In our study, isolates were not resistant to azithromycin, ceftiofur, or ceftriaxone either before or after either ceftiofur or tulathromycin treatment. This result was supportive of metagenomic data analyses conducted by Weinroth et al and Doster et al but counter to the findings of Alali et al (33)(34)(35). The studies measured the effect of either ceftiofur or tulathromycin treatment on the microbiome and/or resistome of the fecal community of beef cattle; however, none of the studies focused directly on culturable bacteria, let alone Salmonella, as the outcome bacteria of interest.…”
Section: Discussionsupporting
confidence: 53%
“…According to their findings, ceftiofur treatment increased resistant E. coli populations after treatment; however, they observed that the population returned to preadministration resistance levels after a 2-week period. Weinroth et al also investigated the effects of ceftiofur use on the resistome of cattle feces, focusing on the bla CMY-2 and bla CTX-M-24 genes in the fecal microbiome on day 0 and day 26 (33). In contrast to the results of Alali et al, but similar to our results, their results did not indicate any significant changes in ceftriaxone resistance over a 26-day period, though they did not analyze the samples taken during peak antibiotic activity (i.e., days 4 to 12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ResFinder -Metagenomic read-mapping outperformed cultivation-based techniques in terms of predicting expected tetracycline resistance based on farm antimicrobial consumption Weinroth et al (2018) Bovine faecal samples during a clinical trial using ceftiofur and chlortetracycline MEGARes -Treatment with ceftiofur was not associated with changes in b-lactam resistance genes -Treatment with chlortetracycline had a significant increase in relative abundance of tetracycline resistance genes -There was an increase in resistance to an antimicrobial class not administered during the study, which is a possible indication of co-selection of resistance genes Munk et al (2018) Samples from pig and poultry farms ResFinder -Higher AMR gene loads were observed in pig farms, whereas poultry resistomes were more diverse -Several critical AMR genes, including mcr-1 and optrA, were detected, the abundance of which differed both between host species and between countries -The total acquired AMR genes level was associated with the overall country-specific antimicrobial usage in livestock The main advantages of shotgun metagenomics over classical methods for analysing the resistome is that this methodology is faster, allows for the simultaneous detection of a vast number of resistance genes of different microbial origins within a given sample and the estimation of their relative abundance, and in some cases it is possible to get important information on the genetic background of the detected AMR determinants (microbial species or strain of origin and/or association with mobile genetic elements, such as plasmids, integrons, transposons, prophages, etc.). In fact, shotgun metagenomics can be also used to characterise the so-called mobilome (pool of mobile genetic elements) in a given sample (Ravi et al, 2017).…”
Section: Metagenomics In Food-borne Outbreak Detection/investigationmentioning
confidence: 99%